2022
DOI: 10.3389/fpls.2022.921937
|View full text |Cite
|
Sign up to set email alerts
|

Genome Size Variation and Evolution Driven by Transposable Elements in the Genus Oryza

Abstract: Genome size variation and evolutionary forces behind have been long pursued in flowering plants. The genus Oryza, consisting of approximately 25 wild species and two cultivated rice, harbors eleven extant genome types, six of which are diploid (AA, BB, CC, EE, FF, and GG) and five of which are tetraploid (BBCC, CCDD, HHJJ, HHKK, and KKLL). To obtain the most comprehensive knowledge of genome size variation in the genus Oryza, we performed flow cytometry experiments and estimated genome sizes of 166 accessions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 106 publications
0
10
0
Order By: Relevance
“…Notably, in land plants, there is a, 2400-fold variation of genome size between different species ( Pellicer et al., 2018 ), which has been shown to be caused by lineage-specific insertion/excision dynamics of DNA elements such as retrotransposons ( Bennetzen et al., 2005 ; Grover et al., 2008 ; Pellicer et al., 2018 ; Chase et al., 2023 ). For example, genome size increases have been related to retrotransposon invasions in Poaceae ( Sanmiguel and Bennetzen, 1998 ; Hawkins et al., 2006 ; Piegu et al., 2006 ; Dai et al., 2022 ), Melanthiaceae ( Pellicer and Leitch, 2014 ; Pellicer et al., 2021 ) or Gymnosperms ( Morse et al., 2009 ; Ohri, 2021 ). In addition to retrotransposon invasions, giant genomes are thought to have arisen because of the lack of DNA removal ( Kelly et al., 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…Notably, in land plants, there is a, 2400-fold variation of genome size between different species ( Pellicer et al., 2018 ), which has been shown to be caused by lineage-specific insertion/excision dynamics of DNA elements such as retrotransposons ( Bennetzen et al., 2005 ; Grover et al., 2008 ; Pellicer et al., 2018 ; Chase et al., 2023 ). For example, genome size increases have been related to retrotransposon invasions in Poaceae ( Sanmiguel and Bennetzen, 1998 ; Hawkins et al., 2006 ; Piegu et al., 2006 ; Dai et al., 2022 ), Melanthiaceae ( Pellicer and Leitch, 2014 ; Pellicer et al., 2021 ) or Gymnosperms ( Morse et al., 2009 ; Ohri, 2021 ). In addition to retrotransposon invasions, giant genomes are thought to have arisen because of the lack of DNA removal ( Kelly et al., 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…Further, considering the evolution of the Oryza spp. (i) Comparative genomic fingerprints strongly support an independent evolution of Oryza species [47]. (ii) Before the onset of the worldwide distribution of O. sativa about 300 years ago, the geographic isolation of many rice species and short-lived pollen at least in Oryza sativa represented constraints making cross-continental interspecific hybridization within the genus Oryza by long-range transport of pollen.…”
Section: Discussionmentioning
confidence: 94%
“…As a result, it must sustain extreme conditions, which include cold winter and hot and dry summer with annual temperatures commonly varying from 0 °C to 30 °C. Abiotic stressors have been recently implicated in genome size fluctuation and evolutionary trade-offs [ 69 , 70 , 71 , 72 ]. Recently it was also reported that genome size in plants can influence the stress tolerance of invasive and native plants via genomic plasticity [ 69 ].…”
Section: Discussionmentioning
confidence: 99%